Watering the Grassroots: A Strategy for Social Movement Support - and Joyce, Mary (Transparency & Accountability Initiative, 2015)
In this third and final think piece exploring the role of grassroots organizations and movements for state accountability (find the previous pieces here and here), the author Mary Joyce, proposes new thinking about how funders and other external organizations can best support social movements. Funding and other support for popular organizations and movements is not straightforward, and there are potential risks and distortions involved. Interested supporters need to clearly identify and articulate these obstacles in their discussions with movement activists before pursuing and funding or other support activities. This think piece outlines several potential avenues of support: small, flexible grants; funding intermediary organizations; providing external consultants or researchers to work with movements; and other options as well. These suggestions provide ideas for funders and other organizations seeking to move beyond projects to supporting robust accountability ecosystems, in which grassroots organizations and movements play a critical role.